The Role of Job Satisfaction in Mediating The Relationship of Organizational Culture and Work Discipline on Employee Performance in The General Section of The Raja Ampat Regional Secretariat - Ida Bagus Udayana Putra; Indra Setia Ganda (Jurnal Ekonomi dan Bisnis Jagaditha, 2024)
Effective human resource management is reflected in the achievement of optimal performance by employees, which supports the company's growth and success. Therefore, it is important for every company to explore human resource development strategies aimed at improving employee performance and ensuring their comfort in carrying out their duties. This research aims to analyze the influence of organizational culture and work discipline on employee performance by mediating employee job satisfaction in the General Section of the Raja Ampat Regency Regional Secretariat. The population used was all employees of the General Section of the Raja Ampat Regional Secretariat, namely 44 employees. The number of samples used was 44 employees with a sampling technique using a saturation technique. The data analysis used in this research is inferential analysis using SEM-PLS. The results of this research show that Organizational culture has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on job satisfaction. Work Discipline has a positive and significant effect on Employee Performance. Work Discipline has a positive and significant effect on Job Satisfaction. Job satisfaction has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance through Job satisfaction. Job satisfaction partially mediates (partial mediation) between organizational culture and employee performance. Work Discipline has a positive but not significant effect on Employee Performance through Job satisfaction. Job satisfaction is not able to mediate (Unmediated) between Work Discipline on Performance Employee.